Table of Content - -, (Journal of Educational and Psychological Sciences, 2024)
Table of Content:1. Digital Leadership and its Relationship to Change Management among Female Principals of Public Primary Schools in Riyadh CityMs. Fadaha Saeed Al-Qahtani, Dr. Hessh Saad Al-Arifi2. The Level of Dialogue Skills for Tenth and Eleventh-Grade Students in Al-Batinah North Governorate Schools in the Sultanate of Oman from Their PerspectiveMr. Mohammed Salim Ali Al-Jahwari, Prof. Jawhar Abdul Qadir Al-Jammoussi3. The impact of modern trends in education on the use of learning strategies for people  with mental disabilities for the secondary stage from the point of view of teachers  in the city of MakkahMs. Hanaa Fahad Al-Sowat4. Obstacles to the implementation of professional learning communities among UNRWA school teachers in the Jerusalem; Jericho Area from teachers’ perspectiveDr. Sahar Said Marbou5. The Relationship between Positive Thinking and Psychological Health Dimensions in Female Students at the College of Education, Hail UniversityMs. Malkah Murdhi Almutawaa6. Successful Intelligence and its Relationship to the Cognitive Holding Power among Umm Al-Qura University Female StudentsMs. Asmaa Mohammad Hashem Azouz , Prof. Nawar Mohammad Saad Al-Harbi7. Refocusing Positively and Its Relationship With (Analytic–Global) Cognitive Style Among University StudentsDr. Salwa Faiq Abd8. Education Between Entertainment and Training: An Applied Study on Public Schools  in Mahayel Asir ProvinceMs. Layla Ahmed Al-Habiri
Keywords: Journal of Educational and Psychological Sciences